2016
DOI: 10.1002/app.43882
|View full text |Cite
|
Sign up to set email alerts
|

Poly1‐hexene: New impact modifier in HIPS technology

Abstract: Poly1-hexene was prepared using a conventional heterogeneous Ziegler-Natta catalyst and its stereoregularity was characterized using 13 C-NMR analysis. New kind of high impact polystyrene (HIPS) was prepared by radical polymerization of styrene in the presence of different amounts of synthesized poly1-hexene (PH) as impact modifier (HIPS/PH) and compared with conventional high impact polystyrene with polybutadiene (HIPS/PB) as rubber phase. Scanning electron microscopy (SEM) revealed that the dispersion of pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 44 publications
1
21
0
1
Order By: Relevance
“…This dilatational stress increased free volume in the rubbery phase and allowed reduction of the relaxation time of the rubbery chains and therefore, reduced the T g of the corresponding phase . Another important point is that lowering of T g is the proof of appropriate dispersion of plasticizing rubber particles in the PS matrix …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This dilatational stress increased free volume in the rubbery phase and allowed reduction of the relaxation time of the rubbery chains and therefore, reduced the T g of the corresponding phase . Another important point is that lowering of T g is the proof of appropriate dispersion of plasticizing rubber particles in the PS matrix …”
Section: Resultsmentioning
confidence: 99%
“…6 Another important point is that lowering of T g is the proof of appropriate dispersion of plasticizing rubber particles in the PS matrix. 8 DSC analysis was performed to confirm the reduction of T g of rigid PS matrix upon blending with elastomer particles (see Figure 8). Kim and his coworker reported that glass transition temperature of PB remains essentially unchanged with weight fraction in the PS/PB blends; however, the T g of PS changes considerably by altering its content.…”
Section: Dmta and Dscmentioning
confidence: 99%
See 3 more Smart Citations